Comparative analysis of three methods for HPV DNA detection in cervical samples - Michelli, Elvia; Téllez, Luis; Mendoza, José Andrés; Jürgensen, Claudia; Muñoz, Maritza; Pérez, Saberio; Mosqueda, Noraida; Hernández, Erick; Noguera, María Eugenia; Callejas, Diana; Correnti, María; Cavazza, María Eugenia; et al. (Investigación Clínica, 2012)
High risk HPV infection is considered to play a central role in cervical carcinogenesis. HPV DNA testing has shown to be a very useful tool for screening and following cervical infections. The aim of this study was to compare three methods for HPV DNA detection, along with cytology and colposcopy analysis. Cervical samples were collected from 100 sexually active women in Mérida, western Venezuela. HPV infection was screened using Hybrid-Capture 2 (HC2), L1-Nested-PCR and E6/E7-PCR assays. 40% of the samples (40/100) were HPV positive by at least one of the DNA detection methods. HC2 detected HPV in 12% specimens. L1- and E6/E7-PCRs showed 50% sensitivity and 77% specificity.The agreement rate between HC2 and both PCR assays was 65%. Kappa value showed moderate concordance between HC2 and both PCR methods (ïŸ=0.55; CI 95%). Also moderate concordance was seen when L1- and E6/E7-PCRs were compared (ïŸ=0.48; CI 95%). There was a significant association between the Schiller test and E6/E7-PCR (p=0.006) for HPV infection. An acceptable agreement between all three assays for HPV detection was observed. Nevertheless, different PCR formats need to be further analyzed in order to make the right choice of method for HPV testing.